A low preoperative platelet-to-white blood cell ratio is associated with acute kidney injury following cerebral aneurysm treatment in South Korea - Seung-Woon Lim; Woo-Young Jo; Hee-Pyoung Park (Acute and Critical Care)
Background Inflammation is involved in the pathophysiology of postoperative acute kidney injury (AKI). We investigated whether preoperative platelet-to-white blood cell ratio (PWR), a novel serum biomarker of systemic inflammation, was associated with postoperative AKI following cerebral aneurysm treatment. We also compared the discrimination power of preoperative PWR with those of other preoperative systemic inflammatory indices in predicting postoperative AKI. Methods Perioperative data including preoperative systemic inflammatory indices and cerebral aneurysm-related variables were retrospectively analyzed in 4,429 cerebral aneurysm patients undergoing surgical clipping or endovascular coiling. Based on the cutoff value of preoperative PWR, patients were divided into the high PWR (≥39.04, n=1,924) and low PWR (<39.04, n=2,505) groups. After propensity score matching (PSM), 1,168 patients in each group were included in the data analysis. AKI was defined according to the Kidney Disease Improving Global Outcomes guidelines. Results Postoperative AKI occurred more frequently in the low PWR group than in the high PWR group before PSM (45 [1.8%] vs. 7 [0.4%], P<0.001) and after (17 [1.5%] vs. 5 [0.4%], P=0.016). A low preoperative PWR was predictive of postoperative AKI before PSM (odds ratio [95% CI], 3.93 [1.74–8.87]; P<0.001) and after (3.44 [1.26–9.34], P=0.016). Preoperative PWR showed the highest area under the curve for postoperative AKI (0.713 [0.644–0.782], P<0.001), followed by preoperative platelet-to-neutrophil ratio (0.694 [0.619–0.769], P<0.001), neutrophil percentage-to-albumin ratio (0.671 [0.592–0.750], P<0.001), white blood cell-to-hemoglobin ratio (0.665 [0.579–0.750], P<0.001), neutrophil-to-lymphocyte ratio (0.648 [0.569–0.728], P<0.001), and systemic inflammatory index (0.615 [0.532–0.698], P=0.004). Conclusions A low preoperative PWR was associated with postoperative AKI following cerebral aneurysm treatment.